Strategi Fundraising Digital Dalam Meningkatkan Penghimpunan Dana Ziswaf Program Pemberdayaan Ekonomi Pada Koperasi Syariah Baitul Maal Wat Tamwil - Mohammad Zainuri; Fitriyana Agustin; Robiatul Adawiyah (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2022)
Sharia cooperatives in Indonesia are often called Baitul Maal Wat Tamwil, sharia cooperatives are almost the same as conventional cooperatives where the prominent difference is that baitul maal wat tamwil plays a role in managing zakat, infaq, shadaqah, and waqf funds. If you look more closely at the management of Baitul Maal Wat Tamwil in collecting Zakat, Infaq, Shadaqah, and Waqf funds, it is still lacking, for that it is necessary to implement a digital fundraising strategy in its collection. In the process of digital fundraising strategy activities, an institution or organization must always carry out socialization, education, promotion activities that are packaged in technology. Where the purpose of implementing this strategy is to increase the collection of Zakat, Infaq, Sadaqah, and Waqf funds. In addition, other goals are to improve the image of Baitul Maal Wat Tamwil and help the underprivileged. From the qualitative writing method of the literature that the author uses, the discussion obtained about the methods used in digital fundraising strategies to increase the collection of Zakat, Infaq, Shadaqah, and Waqf funds there are eight methods including, website method, e-mail method, search engine marketing method, social networking method, Islamic bank e-channel method, online website shopping method, e-wallet or electronic wallet method, method of making own application. The hope of implementing this method is to increase the collection of Zakat, Infaq, Shadaqah, and Waqf funds in Baitul Maal Wat Tamwil. So that later Baitul Maal Wat Tamwil will be able to help alleviate poverty and help capitalize on micro and small businesses in Indonesia.